Non-alcoholic fatty liver disease across endocrinopathies: Interaction with sex hormones - Arefhosseini, Sara; Ebrahimi-Mameghani, Mehrangiz; Najafipour, Farzad; Tutunchi, Helda (Frontiers in Endocrinology, 2022)
Abstract Nonalcoholic fatty liver disease (NAFLD) has emerged as the most frequent chronic liver disease globally. NAFLD is strongly associated with metabolic syndrome and it has been recently suggested that to rename NAFLD as metabolic dysfunction-associated fatty liver disease (MAFLD). NAFLD has been studied in different endocrine axes and accumulating body of clinical and experimental studies have suggested that NAFLD is closely associated with polycystic ovarian syndrome (PCOS), hypopituitarism, growth hormone deficiency (GHD), hypogonadism and other endocrine disorders. In fact, endocrine dysfunction may be considered as the major contributor for the development, progression, and severity of NAFLD. In the present comprehensive review, we discussed the epidemiological and clinical evidence on the epidemiology, pathophysiology, and management of NAFLD in endocrine disorders, with an emphasis on the effects of sex-specific hormones/conditions as well as molecular basis of NAFLD development in these endocrine diseases.